Immature forms of low density granulocytes are increased in acute myeloid leukemia and myelodysplastic syndromes - Angela Bertolini; Francesca Picone; Idalucia Ferrara; Anna Maria Della Corte; Bianca Serio; Marisa Gorrese; Annapaola Campana; Vittorio Simeon; Serena Luponio; Rossella Marcucci; Pasqualina Scala; Maddalena Langella; et al. (Scientific Reports)
Abstract Neutrophils can promote or suppress tumor growth. These different immunological functions mirror a great heterogenicity of neutrophil maturation and activation status: low-density granulocytes (LDGs) and normal-density neutrophils (NDNs). LDGs participate in immune dysregulation during autoimmune disorders with an activated phenotype, while NDNs might exert immunosuppressive activities. Here, we investigated variations in distribution of LDGs and NDNs in benign and malignant hematological conditions using an optimized 10-color flow cytometry staining for immunophenotyping of the main circulating populations. A total of 102 consecutive subjects diagnosed with hematological malignancies was enrolled for immunophenotyping by flow cytometry. We showed impaired neutrophil subset distribution in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) patients compared to healthy individuals, with intermediate and mature LDGs significantly reduced, also displaying a good diagnostic sensitivity in MDS (AUC, 0.793 and P = 0.0013; and AUC, 0.7319 and P = 0.0109, respectively) and AML (AUC, 0.9059 and P = 0.0069; and AUC, 0.9176 and P = 0.00057, respectively). In conclusion, LDG and NDN subsets could be altered in AML and MDS, in favor of more immature forms, suggesting that emergency hemopoiesis could be a first mechanism to sustain peripheral blood counts, while maintaining a pro-inflammatory microenvironment.